Bimbingan Membaca Al-Qur’an Kepada Lansia di Desa Tambalang Oleh Mahasiswi KKN Sekolah Tinggi Ilmu Al-Quran (STIQ) Amuntai Tahun 2021 - Syarifuddin; Rizqa Hidayati; Munawarah; Norlaila; Nor Hidayah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2021)
In line with the increasing age of a person and the deterioration process followed by the emergence of cognitive impairment, the decline in cognitive function in the elderly can be prevented by reading the Qur'an, one of which. An elderly person who wants to learn to read the Qur'an properly and correctly must have their own difficulties, but behind that there are always supporting factors that make the elderly continue to be enthusiastic about learning and obstacles in the learning process. The community service subjects were 10 elderly in Tambalang village who wanted to learn to read the Qur'an. The data obtained came from direct activities and direct interviews. Activities run with classical learning. The difficulty of the Tambalang elderly in learning to read the Koran is that it is difficult to pronounce bold letters such as the letter, in distinguishing any similar sound of letters, in determining ikhfa haqiqi and ikhfa syafawi, determining where the recitation stops and repeating it, adjusting the length of the mad, the lack of pressure on the gunnah, in reflecting the letter qalqalah. The supporting factors are being able to read the Qur'an well and correctly from a young age, always being enthusiastic and trying hard, having high motivation. The inhibiting factor is blurred vision, it has been a long time since learning to read the Qur'an, teeth have fallen out.